ANALISIS KONDISI FISIK ATLET BOLAVOLI PUTRA DARAMISTA SUMENEP - Hairil Fani (Jurnal Pedagogik Olahraga, 2026)
Sports are physical activities conducted according to specific rules and procedures, with the primary goal of improving physical performance and maintaining a stable level of performance during volleyball matches. Excellent physical condition is a crucial factor that every player must possess. The physical fitness components that play a significant role in volleyball include strength, endurance, lower-body explosive power, speed, and agility. The objective of this study is to assess the physical fitness of the Putra Daramista Sumenep men’s volleyball team. This study employed a quantitative descriptive method and was conducted at a single time at the PBV Putra Daramista Sumenep court. The sample size for this study was 15 athletes. Data collection involved the following tests and measurements: speed test (10-meter sprint), agility test (T-test), strength test (push-ups and sit-ups), power test (vertical jump), and cardiovascular endurance test (MFT). The results obtained were, on average, in the “below average” category, with the Putra Daramista volleyball athletes achieving the following scores: 1) speed (2.10 seconds), 2) agility (12.59 seconds), 3) push-ups (18 repetitions), 4) sit-ups (16 repetitions), 5) vertical jump (56.15 cm), 6) MFT (33.9). The conclusion drawn is that the male volleyball athletes of Daramista Sumenep have a physical condition categorized as “poor,” thus requiring the development of physical conditioning training, particularly in agility, lower-body explosive power, cardiovascular endurance, and abdominal muscle strength.